ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJEMEN AKIBAT PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Dharmayanti, Ni Made; Suardhika, Made Sadha (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
Purpose of this study was to`determine the effect simultaneously on factors user involvement in the development of accounting information system, personal technical ability, the size of the company, as well as the support of top management on the performance of management as a result of the use of accounting information system on rural banks. Location in this study are rural banks city of Denpasar Bali is the object of study is the management and analysis of performance factors Rural Bank city of Denpasar Bali province. A total population of 286 employees and the number of respondents who used are 52 employees. The analysis technique used in this study is the technique of multiple linear regression analysis. Based on the results of data analysis know user involvement in the development of accounting information systems, personal technical ability, the size of the company, an top management support simultaneous effect on performance management.
Keywords: Perfomance Management, Accounting Information Systems, Personal Technikal Ability, The Size Of the Company, and The Support Of Top Management